Source Its types, and its usual rank (Journal of the College of Basic Education, 2022)
Praise be to God, a praise worthy of His greatness and majesty, and the best prayer and the most complete salutation to the Holy Prophet. Muhammad bin Abdullah, his good and pure family and his chosen companions.This research is entitled (the infinitive .. its types and the order of its action), and it is in grammatical studies. The research was concerned with showing the definition of the infinitive and limiting its three types, and it examined in detail the aspects of the order of its factors in advance and in delay, whether the infinitive is taken from an intransitive verb or from a transitive verb, and the speech has been reinforced in The search is based on the sayings of the advanced grammarians in the case of affirmation and negation, and the research also discussed the sayings of the grammarians in this regard, relying on the Holy Qur’anic text mainly in citation and response, then on verses of poetry,